(untitled) (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted to reuse waste generated from mushroom farm called composted spent mushroom substrate (SMS) as casing material for the production of milky white mushroom. The production trial of milky white mushroom was conducted with five casing mixture viz. Loam soil + Sand (3:1) (farmer’s practice), SMS compost + Sand (3:1), Loam soil + SMS compost + Sand (2:1:1), Loam soil + SMS compost + FYM (1:1:1) and SMS compost + FYM (1:1). Results revealed the suitability of SMS to reuse as casing materials through composting. Casing treatments containing SMC alone or combination with sand (3:1) and soil + FYM (1:1:1) produced statistically similar yield which were statistically higher than farmer’s practice. Among these three treatments, pH, EC, particle density and organic carbon ranged between 7.16-7.82, 1.69-1.84 mmhos cm−1, 1.52-1.90 g cc−1 and 11.3%-15.8%, respectively. Below or above this range reduced the yield of milky white mushroom. SMC, SMC + Sand (3:1) and Soil + SMC + FYM (1:1:1) produced statistically similar yield but SMC and SMC + Sand (3:1) took shorter time to harvest than Soil + SMC + FYM (1:1:1). So, SMC or SMC + Sand (3:1) can be recommended to use as casing material. J. Bangladesh Agril. Univ. 15(2): 239-247, December 2017